Effect of Financing To Deposit Ratio (FDR), Return On Assets (ROA), and Third Party Fund (TPF) on Mudharabah Financing in Islamic Banking - Mohamad Zulman Hakim; Nur Fizriati Ananda; Hesty Erviani Zulaecha; Dewi Rachmania; Hamdani Hamdani; Mikrad Mikrad (Cita konsultindo, 2023)
This study aims to determine the effect of Financing to Deposit Ratio, Return On Assets, Third Party Funds on mudharabah financing. The population in this study is Islamic Commercial Banks registered with the Financial Services Authority (OJK) for the period 2017-2021. The sampling technique used purposive sampling technique. The results in this study are (1) FDR has an effect on mudharabah financing, (2) ROA has no effect on mudharabah financing, (3) TPF has an effect on mudharabah financing.